The Gates Effect in Public Goods Experiments: How Donations Flow to the Recipients Favored by the Wealthy - Luca Corazzini; Christopher Cotton; Enrico Longo; Tommaso Reggiani (Masaryk University, Faculty of Economics and Administration, 2021)
Experiments involving multiple public goods with contribution thresholds capture many features of charitable giving environments in which donors try to coordinate their contributions across various potential recipients. We present results from a laboratory experiment that introduces endowment and preference differences into such a framework to explore the impact of donor heterogeneity on public good success and payoffs. We observe that wealthier donors tend to provide larger contributions to the public goods, and that the contributions of all other donors are most likely directed to the public good preferred by the wealthiest donor as other group members try to coordinate their donations to ensure public good success. We refer to this collective focus on the preferred good of the wealthiest as the Gates Effect. The Gates Effect can reduce inequality among donors groups that succeed in funding a public good; however, it also affects the philanthropic agenda, reducing the variety of public goods that receive funding.
Keywords: C91; C92; H40; H41; L31; 330; Multiple public goods; Donor heterogeneity; Crowdfunding; Charitable giving; Philanthropy; Lab experiment